An alternative model for the role of salt depositional configuration and preexisting salt structures in the evolution of the Southern Pyrenees, Spain. (May 2021) - Hudec, Michael R.; Dooley, Tim P.; Burrel, Laura; Teixell, Antonio; Fernandez, Naiara
Abstract: Salt depositional configuration exerted a fundamental control on both extensional and contractional deformation in the south-central Pyrenees. We divide the area into three domains and suggest that these domains are inherited from the original configuration of the Triassic Keuper salt basin. The Northern and Southern Domains are salt-diapir provinces with complex Mesozoic growth histories, whereas the Central Domain separating them has no diapirs and simpler Mesozoic isopachs. We use these patterns to interpret the Northern and Southern Domains as transported salt basins that were originally separated by the Central Horst, on which salt was thinner. During Dogger to mid-Cenomanian rifting, the Southern Salt Basin was an interior basin, isolated from deformation in the rift axis, whereas the Northern Salt Basin hosted an extensional breakaway at the updip end of the axial rift. During Pyrenean shortening, regions with preexisting salt structures were preferentially reactivated, whereas the stronger Central Horst remained relatively rigid. Eventually the sedimentary cover of the Southern Pyrenees was translated southwards and the connection with the original basement structure was lost. We tested our hypotheses using physical models. We confirmed that shortening a network of preexisting salt pillows could generate structures like the dome-and-basin pattern observed in the Southern Domain, and that it is possible to shorten salt basins on either side of a central horst while leaving sediments above the horst relatively undeformed. Highlights: The Southern Pyrenees can be divided into three domains based on salt tectonics. The Southern Pyrenees comprises two salt basins separated by a horst with thin salt. Diapirs in the salt basins were preferentially reactivated during shortening. The Northern Salt Basin was part of a linked kinematic system during rifting. The Southern Salt Basin was an interior basin, isolated from the continental margin.